Exsolution Lamellae in Orthopyroxene of Lherzolite from the Pauza Ultramafic Rocks, Ne Iraq: Evidence of Deep Mantle Signature in the Zagros Suture Zone - Mohammad, Yousif Osman; Aziz, Nabaz Rashid Hama (International Journal of Geography and Geology, 2013)
The Pauza ultramafic body is part of Upper Cretaceous Ophiolitic massifs of the Zagros Suture Zone, NE Iraq. The present study reveals evidence of Ultra-high pressure (UHP), and deep mantle signature of these peridotites in the Zagros Suture Zone throughout the observation of backscattered images and micro analyses which have been performed on orthopyroxen crystals in lherzolite of Pauza ultramafic rocks.Theorthopyroxen shows abundant exsolution lamellae of coarse unevenly distributed clinopyroxene coupled with the submicron uniformly distributed needles of Cr-spinel. The observed clusters of Opx–Cpx–Spl represent the decompression products of pyrope-rich garnet produced as a result of the transition from ultra-high pressure garnet peridotite to low-pressure spinel peridotite (LP). Neoblastic olivine (Fo92 – 93) with abundant multi-form Cr- spinel inclusions occurs as a fine-grained aggregate around orthopyroxene, whereas coarse olivine (Fo90-91) free from chromian-spinel is found in matrix. The similarity of the Cr-spinel lamellae orientations in both olivine and orthopyroxene, moreover, the enrichments of both Cr and Fe3+ in the Cr-spinel inclusions in neoblastic olivine relative to Cr-spinel lamellae in orthopyroxene, suggest that spinel inclusions in olivine have been derived from former Cr-spinel lamellae in orthopyroxene. Neoblastic olivine is formed by reaction of silica-poor ascending melt and orthopyroxene. It is inferred that the olivines with multi-form spinel inclusions has been formed by incongruent melting of pre-existing spinel lamellae-rich orthopyroxene.